Predictive Torque Control with Simple Duty-Ratio Regulator of PMSM for Minimizing Torque and Flux Ripples - Adase, Leticia Aseye; Alsofyani, Ibrahim Mohd; Lee, Kyo Beum (IEEE Access, 2020)
In this paper, a new method for reducing the ripples of torque and flux is proposed for the predictive torque control (PTC) of permanent magnet synchronous motors. The conventional PTC uses equations to analyze the relationship between the electrical torque and voltage with a fixed magnitude of reference voltage. Consequently, flux and torque ripples increase significantly at low-speed operation. This paper proposes an improved PTC algorithm using a simple duty-ratio regulator. The proposed method will minimize the torque error by calculating an appropriate torque minimization function to mitigate the induced torque and flux ripple at low speed operation. This torque minimization function is synthesized into the space vector pulse-width modulation block to reduce the torque ripple induced owing to the fixed time duration. The proposed scheme considerably reduces the torque and flux ripples and establishes a fast-dynamic response of the torque in the transient state. Simulation and experimental results show that the proposed method achieves a more efficient steady-state performance and a faster step response compared with the conventional PTC.
Keywords: Fast dynamic response; Flux ripple; Minimization function; Permanent Magnet Synchronous Motor; Predictive torque controls; Space vector pulse width modulation; Steady state performance; Torque-ripple reduction; Flux ripple reduction; permanent magnet synchronous motor; predictive torque control; torque ripple reduction